An observational study of sleep in childhood post‐neonatal encephalopathy. (20th May 2021) - Zareen, Zunera; Allen, John; Kelly, Lynne A.; McDonald, Denise; Sweetman, Deirdre; Molloy, Eleanor J.
Abstract: Aim: Neonatal encephalopathy (NE) is associated with altered cognitive, motor, sensory abilities and behavioural outcomes. This case‐control study aimed to assess whether Quality of Life (QoL) and sleep disorders are affected in older children following NE compared to age‐matched controls. Methods: Children at school‐age post‐NE were recruited and compared to age‐matched controls. Sleep and QoL were assessed with the Pediatric Quality of Life Inventory and the Child Sleep Habit Questionnaire. Results: One hundred children were recruited with an age range of 4–6 years, including children post‐NE (n=45) and age‐matched controls (n = 55). Significantly higher pathological sleep scores were evident in 58% of children post‐NE compared to controls (43.8 vs 40.2; p  = 0.001). Children post‐NE had increased bedtime resistance ( p  = 0.028) and sleep anxiety ( p  = 0.01) compared to controls. Children in the post‐NE group had lower total QoL scores versus controls (mean score 82.5 vs 95.8; p  < 0.01). Children with mild NE also had lower total QoL scores than controls (90.0 vs 95.8, p  = 0.003). There was a strong correlation between low QoL with high total sleep scores (Rho 0.339, p  = 0.014). Conclusion: There were high rates of sleep issues in school‐aged children with mild and moderate‐severe NE. Consideration and management of sleep problems may improve QoL in childhood post‐NE.